Horacio y las viejas libidinosas - Suárez Martínez, Pedro Manuel (Estudios clásicos, 1994)
Studying the epodes VIII and XII and the odes I 25, III 15 and IV 13 the author thinks that Horace has reelaborated in the latter the subject of the former. The author underlines that in any case Horace has followed Greek patterns.